Proof of concept: could snake venoms be a potential source of bioactive compounds for control of mould growth and mycotoxin production - Verheecke-Vaessen, Carol; Monte, J.; García-Cela, Esther; Magan, Naresh; Medina, Angel (Wiley, 2020)
The objective was to screen 10 snake venoms for their efficacy to control growth and mycotoxin production by important mycotoxigenic fungi including Aspergillus flavus , Aspergillus westerdijkiae , Penicillium verrucosum , Fusarium graminearum and F. langsethiae . The Bioscreen C rapid assay system was used. The venoms from the Viperidae snake family delayed growth of some of the test fungi, especially F. graminearum and F. langsethiae and sometimes A. flavus . Some were also able to reduce mycotoxin production. The two most potent crude snake venoms (Naja nigricollis and N. siamensis; 41 and 43 fractions, respectively) were further fractionated and 83/84 of these fractions were able to reduce mycotoxin production by >90% in two of the mycotoxigenic fungi examined. This study suggests that there may be significant potential for the identification of novel fungistatic/fungicidal bioactive compounds as preservatives of raw and processed food commodities post‐harvest from such snake venoms.